2016
DOI: 10.3847/2041-8205/829/1/l7
|View full text |Cite
|
Sign up to set email alerts
|

High-Velocity Bipolar Molecular Emission From an Agn Torus

Abstract: We have detected in ALMA observations CO J = 6 → 5 emission from the nucleus of the Seyfert galaxy NGC 1068. The low-velocity (up to ±70 km s −1 relative to systemic) CO emission resolves into a 12×7 pc structure, roughly aligned with the nuclear radio source. Higher-velocity emission (up to ±400 km s −1 ) is consistent with a bipolar outflow in a direction nearly perpendicular ( 80 • ) to the nuclear disk. The position-velocity diagram shows that in addition to the outflow, the velocity field may also contain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
154
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(169 citation statements)
references
References 30 publications
(42 reference statements)
13
154
2
Order By: Relevance
“…A small fraction of the obscuration could come from gas on kpc-scales, as some IR studies have postulated (Deo et al 2007;Goulding et al 2012;Prieto et al 2014). A weak connection may also arise due to the long-lived gaseous inflow patterns between the torus and circumnuclear gas, or due to the molecular emission from the torus itself (Gallimore et al 2016;García-Burillo et al 2016). Modern interferometric observatories such as ALMA will obtain molecular line maps that resolve the inner circum-nuclear region (∼100 pc) for complete samples of nearby AGN.…”
Section: Is Agn Obscuration Related To the Amount Of Cold Gas In A Gamentioning
confidence: 99%
“…A small fraction of the obscuration could come from gas on kpc-scales, as some IR studies have postulated (Deo et al 2007;Goulding et al 2012;Prieto et al 2014). A weak connection may also arise due to the long-lived gaseous inflow patterns between the torus and circumnuclear gas, or due to the molecular emission from the torus itself (Gallimore et al 2016;García-Burillo et al 2016). Modern interferometric observatories such as ALMA will obtain molecular line maps that resolve the inner circum-nuclear region (∼100 pc) for complete samples of nearby AGN.…”
Section: Is Agn Obscuration Related To the Amount Of Cold Gas In A Gamentioning
confidence: 99%
“…For example, NGC 1068 hosts in its center a nuclear torus (García-Burillo et al 2016;Gallimore et al 2016), while NGC 1377 shows a hot compact core dominated by gas along the jet (Aalto et al 2017), which is extremely radio-quiet in contrast to the one in Cen A. A question that remains open is whether this difference reflects different steps in the evolutionary sequence or just simply different scenarios and morphologies.…”
Section: A Lack Of Co/hcomentioning
confidence: 99%
“…These authors found that the redshifted and blueshifted CO J=6-5 emission lines were aligned along the north-south direction, which is highly tilted with respect to the morphologically elongated east-west direction (i.e., the expected torus direction), and interpreted that the molecular gas in the torus is highly turbulent (Garcia-Burillo et al 2016). Gallimore et al (2016) also detected redshifted and blueshifted CO J=6-5 line emission roughly along the north-south direction and argued that the detected emission originated from bipolar outflow activity in the direction almost perpendicular to the torus. The dynamical origin of the compact CO J=6-5 line emission is not clear, and the CO J=6-5 emission could be largely affected by highly excited molecular gas in the outflow.…”
Section: Introductionmentioning
confidence: 99%